Stenodema longicuneata (Carvalho and Rosas, 1966) (Hemiptera, Heteroptera, Miridae) in Patagonia: redescription, new synonym and geographic distribution - Pereyra, Pablo Martín (2019)
The genus Stenodema Laporte, 1832 is a group of grass-feeding plant bugs worldwide distributed, with five species recorded for the Subantarctic sub-region (sunsu Morrone 2015). Males of Stenodema longicuneata (Carvalho and Rosas, 1966) are redescribed and photographed. Stenodema laolaoensis (Carvalho, 1985) is proposed as a junior synonym of S. longicuneata. New geographic records are provided and distributional and biogeographic issues are discussed.